Do Firms Gain from Managerial Overconfidence? The Role of Severance Pay - Clara Graziano; Annalisa Luporini (Center for Economic Studies and ifo Institute (CESifo), 2022)
We analyze the effects of optimism and overconfidence when the manager's compensation package includes severance pay and the CEO has bargaining power. We find that optimism does not affect incentive pay but increases severance pay with a negative effect on profit. Overconfidence, on the contrary, reduces incentive pay as shown by the previous literature, while its effect on severance pay depends on the intensity of the bias. High values of overconfidence yield an inefficient level of investment which in turn increases severance pay with a negative impact on firm profit. Thus, the attempt to exploit managerial overconfidence to reduce incentive pay may back.re if the manager is replaced and severance agreements come into effect. Our model explains the large severance payments documented by empirical literature by showing that discretionary pay in excess of contractual severance pay may represent a form of efficient contracting when the manager is overconfident and optimist.
Keywords: J33; D86; D90; L21; 330; overconfidence; optimism; managerial compensation; severance pay; entrenchment